Effects of Kinesio Taping on the muscular performance of women with chronic lower back pain - José Roberto de Souza Júnior; Thiago Vilela Lemos; Tânia Cristina Dias da Silva Hamu; Amanda Marques Faria; Amanda Terra Silva; Frederico Igor Ribeiro Calaça; João Paulo Chieregato Matheus (O Mundo da Saúde, 2019)
Nonspecific chronic back pain is defined as a pain in the lumbar region lasting more than 12 weeks, that is not related to specific pathologies. Several resources have been used to treat the different aspects of these patients (pain, disability, mobility, strength, endurance, psychological factors, limitation of activities and restrictions in participation), among these, elastic bandages such as Kinesio Taping (KT). The aim of this study was to evaluate the immediate effects of Kinesio Taping on muscle strength, activity, and fatigue of spinal erectors of subjects with nonspecific chronic lower back pain. An isokinetic dynamometer and a surface electromyograph were used to evaluate the study outcomes. The force was measured by means of the peak torque, the activity was through the Root Mean Square and the muscular fatigue was by the median frequency. The Kinesio Taping elastic bandage was applied in an "I" for aiding the spine erectors according to the recommendations of the method. The subjects were evaluated with and without the KT bandage. The data were analyzed in the SPSS (Statistical Package for Social Sciences) version 23.0 considering p <0.05. The sample consisted of 34 women with a mean age of 21.14 years (2.64) and a Body Mass Index (BMI) of 21.54 kg/m². No significant differences were found in strength, activity and muscle fatigue when comparing the evaluations performed with and without the bandage (p>0.05). It was concluded that elastic bandaging does not present immediate effects on muscle strength, activity, and fatigue of the spinal erectors of subjects with nonspecific chronic lower back pain.